An unusual complication of ventriculoperitoneal shunt with bladder perforation and extrusion through the urethra orifice in an adult male patient. (2nd January 2019) - Yang, Xiang; Liang, Ruofei; Zhang, Yuekang
Abstract: A 29-year-old male exhibited progressive extrusion of the distal end of ventriculoperitoneal (VP) shunt through his urethral orifice within 10 d. The distal end of VP shunt was pulled out from the urethral orifice without bladder repairment, a new VP shunt assisted with ventriculoscope and laparoscope was performed and the distal end of VP shunt was fixd to the suprahepatic space. We first report a chronic complication of VP shunt with bladder perforation and extrusion through the urethral orifice in an adult male patient. To avoid this complication, the length of the distal end of VP shunt should be kept as short as possible in adults and we recommend that the distal end of VP shunt should be fixed to the suprahepatic space assisted with laparoscope in adult patients.